Impacts of Early Childhood Marriage in Indonesia Viewed from Child Protection Laws Perspectives - Gunawan, Shella Oetharry; Bahri, Syamsul (El-Usrah: Jurnal Hukum Keluarga, 2023)
This article seeks to elucidate the ramifications of early marriage or child marriage about the Child Protection Law and explicate endeavors to thwart child marriage as a means of safeguarding children. The research method employed is normative juridical, which involves analyzing and evaluating relevant laws and regulations as the major source for problem-solving. The research findings indicate that child marriage violates the Child Protection Law. Moreover, child marriage might impede the realization of children's rights, hence compromising their overall growth and development. Child marriage exerts a significant influence on economic, social, health, educational, and psychological issues. Efforts aimed at preventing child marriage serve as a means of safeguarding children. It is necessary to enhance and unify rules pertaining to the prevention of child marriage. This should involve collaboration across many levels of government, from national to local, and engage all segments of society, particularly young individuals, to effectively execute measures against child marriage. It is advisable to enhance and align the age restrictions for children across rules to ensure they are consistent, mutually reinforcing, and efficiently implemented in practice. There is a requirement for additional regulations concerning marriage dispensation by the District Court or Religious Court. It is also important for Judges to be consistent and firm in their decisions regarding marriage dispensation cases, in line to prevent or reject child marriage as stated in PERMA Number 5 of 2019.